Foreign capital for economic development : - Kim, Seung Hee (Praeger, 1970)
This study attempts to integate the factors that affect the amount of foreign-capital needs in Korea and the forces that determine the parameter values of these factors. The major economic factora discussed in this book are aggregate income, investmant, savings, exports, and imports.